2004
DOI: 10.2134/jeq2004.1779
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Differences in Mercury Tolerance, Accumulation, and Distribution in Willow

Abstract: This study was performed to investigate mercury (Hg) tolerance, accumulation, and translocation within the genus Salix for the potential use of this plant to remediate Hg-contaminated sites. Six clones of willow (Salix spp.) were tested on tolerance to Hg by treating plants grown in solution culture with 0 to 15 microM HgCl(2). Results showed that willow had a large variation in its sensitivity to Hg. However, the accumulation and translocation of Hg to shoots was similar in the eight tested willow clones as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(71 citation statements)
references
References 26 publications
5
62
1
3
Order By: Relevance
“…In fact, PCs were not detected in either sensitive or tolerant willow (Salix spp.) clones in recent reports for Hg (Wang and Greger, 2003) and other metals (Landberg and Greger, 2004).…”
mentioning
confidence: 85%
“…In fact, PCs were not detected in either sensitive or tolerant willow (Salix spp.) clones in recent reports for Hg (Wang and Greger, 2003) and other metals (Landberg and Greger, 2004).…”
mentioning
confidence: 85%
“…In Salix spp. it was proved that the majority of the mercury is accumulated and retained in the cell wall of the roots and only a very small part is trans ferred to the shoots (Wang & Greger 2004).…”
Section: Molecular Biology and Genetic Engineering For Phytoremediationmentioning
confidence: 99%
“…Numerous studies have revealed a remarkable genotypic variability of the genus Salix in its ability to tolerate/accumulate heavy metals (Wang and Greger, 2004;Dos Santos Utmazian et al, 2007;Purdy and Smart, 2008;Zhivotovsky et al, 2010). Most results of willow screening have shown that the tolerance and uptake of heavy metals depend strongly on species and clones (Punshon et al, 1995;Dos Santos Utmazian et al, 2007;Zacchini et al, 2009;Zhivotovsky et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the metal accumulation potential of Salix to identify prospective phytoremediation species/clones through carefully controlled hydroponic screenings (Punshon et al, 1995;Watson et al, 2003;Kuzovkina et al, 2004;Wang and Greger, 2004;Dos Santos Utmazian et al, 2007;Purdy and Smart, 2008;Mleczek et al, 2010;Zhivotovsky et al, 2010). As a rapid screening technology, hydroponic screening reduces the time and space required in comparison with other methods, and is especially suitable for high-throughput screening to evaluate large amounts of plant materials for phytoremediation (Dos Santos Utmazian et al, 2007).…”
Section: Introductionmentioning
confidence: 99%